Circular Airy-like beams through leaky-wave antennas. (23rd February 2023) - Benedetti, Alessio; Comite, Davide; Fuscaldo, Walter; Baccarelli, Paolo; Galli, Alessandro; Burghignoli, Paolo
Abstract: A planar nonuniform radially periodic leaky-wave antenna is proposed for the generation of circular, azimuthally symmetric Airy beams. The design is compact and low cost, and it is excited by an integrated coaxial cable. An annular metal strip grating is considered as background structure, designed to support a fast, backward, radially propagating space harmonic, which is capable of generating nondiffracting fields. The period and slots width are then properly modulated to synthesize the relevant Airy-like aperture-field distribution. An approximate formula is proposed to describe the aperture field, which is then used to retrieve the pattern of the annular strips. The near field produced by the structure is evaluated through the radiation integral, and validated by means of numerical full-wave simulations.